2021
DOI: 10.4142/jvs.2021.22.e66
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing for the genetic characterization of Maedi/Visna virus isolated from the northwest of China

Abstract: Background Maedi/Visna virus (MVV) is a contagious viral pathogen that causes considerable economic losses to the sheep industry worldwide. Objectives In China, MVV has been detected in several regions, but its molecular characteristics and genetic variations were not thoroughly investigated. Methods Therefore, in this study, we conducted next-generation sequencing on an MVV strain obtained from northwest China to reveal its genetic evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Regarding MHR, in our study, medium heterogeneity was presented among the sequences belonging to genotype A, whereas three new replacements were also observed (H/Q, N/D, and K/N). This finding is in accordance with previous studies, which reported moderate variability in the MHR of isolated strains [ 39 , 51 , 60 ]. Even though genotype A strains in our study demonstrated high similarity with the strains previously isolated in Greece, the new unique replacements that were identified could lead to a significant divergence related either to a poor diagnostic performance of serological diagnostic tools based on specific epitopes or to alternative infectivity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding MHR, in our study, medium heterogeneity was presented among the sequences belonging to genotype A, whereas three new replacements were also observed (H/Q, N/D, and K/N). This finding is in accordance with previous studies, which reported moderate variability in the MHR of isolated strains [ 39 , 51 , 60 ]. Even though genotype A strains in our study demonstrated high similarity with the strains previously isolated in Greece, the new unique replacements that were identified could lead to a significant divergence related either to a poor diagnostic performance of serological diagnostic tools based on specific epitopes or to alternative infectivity.…”
Section: Discussionsupporting
confidence: 94%
“…Immunodominant epitopes of capsid protein have been previously characterized in many studies for the assessment of their heterogeneity [ 6 , 7 , 9 , 24 , 34 , 51 , 52 , 53 , 54 ]. Considering that immunodominant linear epitopes of capsid protein are strongly associated with the type-specific host immune response [ 46 , 53 , 55 ], their role in serological diagnosis is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, however, the basal taxa in each clade reflect SRLV diversity found near the extreme Eastern and Western ends of the Eurasian continent. Among A-like SRLVs, basal isolates are linked to regions where fat-tailed breeds have traditionally predominated and include one isolate ‘NM1111’ sampled in the Inner Mongolia region of China ( Zhao et al. 2021 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are still limited complete genome sequences of SRLV. Therefore, it would be desirable to fully sequence the genomes using the recently developed third-generation sequencing technique to investigate recombination frequencies among SRLV ( 179 ).…”
Section: Genetic Diversitymentioning
confidence: 99%